PROBLEM-BASED LEARNING MODEL IN ELPSA FRAMEWORK ON MATHEMATICAL LEARNING PROCESS IN JUNIOR HIGH SCHOOL - Sukasno Sukasno; Drajat Friansah; Lucy Asri Purwasi (Jurnal Infinity, 2018)
The objective of this research was to find out the effectiveness of mathematical learning outcomes to the eighth-grade students after giving treatment by using the problem-based learning model. a pre-experimental method was used in this research. The population of this research was all eighth-grade students of Junior High School. The number of the population was 103 students, while the sample was chosen randomly. The sample of this research was 33 students. Data collection was carried out using a test in the form of an essay. The results of this research showed that it was significantly effective to use problem-based learning model in ELPSA framework to the eighth-grade students of Junior High School. It was proved by the average score of the final test after giving treatment was 79.33 and the total number of students who completed the score was 78.79%.